P526 Social functioning, work-productivity and psychological assessment in a cohort of patients with inflammatory bowel disease: an observational study. (27th May 2021) - Todeschini, A
Abstract: Background: Patients with inflammatory bowel disease (IBD), ulcerative colitis (UC) and Crohn's disease, claims to suffer a significant hindrance in everyday life, because of the frequency of psychological complaints. The aim of this study was to identify and analyze social functioning, work productivity and psychological assessment in IBD patients and to correlate these parameters with history and activity of the disease. Methods: An observational study was performed in 99 IBD patients. Psychosocial data were assessed through the administration of specific questionnaires: Social Functioning Questionnaire (QFS) for monitoring social functioning; Work Productivity and Activity Impairment questionnaire (WPAI) for work productivity; State-Trait Anxiety Inventory (STAI 1, 2), for psychological assessment. IBD activity was measured by Partial Mayo score. Student's t test or Wilcoxon rank sum test were used to compare continuous variables between subgroups and chi-square test to compare categorical variables. Univariate and multivariate linear regression were used, respectively, to assess the relationship between psychosocial and disease characteristics and to compare outcomes with determinant associated results in univariate regression. Results: Univariate analysis showed a statistically significant correlation of the overall QFS score with both the level of education (0.6; 95% CI = 0.1–1.2; p = 0.028) and the unemployed status (- 4.5; 95% CI = -8.9- -0.1; p = 0.044). Moreover, the impairment of WPAI was greater in subjects with ulcerative colitis with severe endoscopic activity according with Partial Mayo score (15.5; 95% CI = 1.0–30.0; p = 0.038). Overall impairment in subjects with stable employment correlated with age (- 0.5; 95% CI = -0.9- -0.1; p = 0.010) and was greater in subjects who underwent at least one surgical operation (15.8; 95% CI = 3.0–28.6; p = 0.016). Psychological evaluation showed that state and trait anxiety correlated significantly with Partial Mayo score (respectively 1.8; 95% CI = 0.6–2.7; p = 0.004 and 1.3; 95% CI = 0.1–2.5; p = 0.042) and age (respectively - 0.2; 95% CI = -0.3- -0.1; p = 0.028 and - 0.3; 95% CI = -0.5 - -0.1; p = 0.037). State anxiety increased in case of long-standing illness (- 0.3; 95% CI = -0.5 - -0.1; p = 0.037), while the non-worker status correlated with trait anxiety when compared to paid employment (- 7.0; 95% CI = -0.9–13.1; p = 0.026). Conclusion: Social functioning was correlated to the employment status and to the level of education. Work productivity was lower in UC patients with severe activity and who undergone at least one surgery related to IBD. The state of anxiety was related with age, duration and activity of illness, while the trait of anxiety was major in non-worker patients.